DATE OF HATE IN SOCIAL MEDIA (FACEBOOK) ACCORDING TO LAW NUMBER 19 OF 2016 CONCERNING ELECTRONIC INFORMATION AND TRANSACTIONS - Yolanda, Nina (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Hate Speech is